The Economic Consequences of Social-Network Structure - Jackson, Matthew O.; Rogers, Brian W.; Zenou, Yves (Journal of Economic Literature, 2017)
We survey the literature on the economic consequences of the structure of social networks. We develop a taxonomy of “macro” and “micro” characteristics of social-interaction networks and discuss both the theoretical and empirical findings concerning the role of those characteristics in determining learning, diffusion, decisions, and resulting behaviors. We also discuss the challenges of accounting for the endogeneity of networks in assessing the relationship between the patterns of interactions and behaviors. (JEL D12, D83, D85, K42, Z13)